International Money Laundering and Its Prevention in the Banking Sector - Purovesi, Riikka (My University, 2016)
Money laundering and especially its sub-division trade based money laundering have been identified as increasing threats to the international economy. Money laundering harms the entire global economy however the knowledge about the nature of money laundering and therefore the actions to prevent it is still at a low level. Trade based money laundering abuses the international trade system and the parties involved in it such as importers, exporters and financial institutions. In the money laundering process the banks can be used as a remittance system and thereby as means to make the illegal money deriving from a criminal act appear clean. Not only the trade finance products but also the other banking products are under the risk of being used in the money laundering process by the criminals. The research tries to find out what are the perceptions of people working closely with anti-money laundering on why, how and what –aspects of trade based money laundering and anti-money laundering. Moreover, the aim was to increase the awareness of trade based money laundering and fill the existing gap within the research on trade based money laundering and anti-money laundering. The research was conducted as interviews with four experts working either in trade finance, compliance, national crime investigation or banking supervision. The aim was to include views from different stages from the anti-money laundering chain. These interviews were conducted as theme interviews and the analysis compared the perceptions from the interviewees to the current available literature and studies. It was noticed during the research that the knowledge among the interviewees was dispersed and especially the money laundering process was unfamiliar and the different phases were not well recognized. However, the signals for the suspicious money laundering cases were widely recognized and they reflected the current literature well. Still, it was noted that at the moment the anti-money laundering process is based on reactive actions instead of being proactive. Therefore, there is a need for more proactive approach to anti-money laundering in order to be able to respond to the increasing threat of money laundering in the international business.